Dietary linoleic acid and the ratio of unsaturated to saturated fatty acids are inversely associated with significant liver fibrosis risk: A nationwide survey - Zhu, Tingting; Lu, Xiao-Ting; Liu, Zhao-Yan; Zhu, Hui-Lian (Frontiers in Nutrition, 2022)
Since no pharmaceuticals have been proven to effectively reduce liver fibrosis, dietary fatty acids may be beneficial as one of the nonpharmaceutical interventions due to their important roles in liver metabolism. In this cross-sectional study, we analyzed data from the 2017-2018 cycle of National Health and Nutrition Examination Survey to examine the associations between the proportion and composition of dietary fatty acid intakes with significant liver fibrosis among U.S. population. The dietary fatty acid consumptions were calculated based on two 24-h dietary recalls. Significant liver fibrosis was diagnosed based on liver stiffness measurement value derived from the vibration controlled transient elastography. Multivariate logistic regression analysis and sensitivity analysis were performed to assess the association between dietary fatty acid consumption and significant liver fibrosis risk. Lastly, restricted cubic spline analysis was carried out to explored the dose-response between polyunsaturated fatty acids (PUFA) or linoleic acid intakes and the risk of significant liver fibrosis. The results showed that the multivariate adjusted odds ratios (95% confidence intervals) of significant liver fibrosis were 0.34 (0.14-0.84), 0.68 (0.50-0.91) and 0.64 (0.47-0.87) for the highest level of unsaturated to saturated fatty acid ratio, dietary PUFA, and linoleic acid intakes compared to the lowest reference, respectively. The sensitivity analysis and restricted cubic spline analysis produced similar results, reinforcing the inverse association of unsaturated to saturated fatty acid ratio, PUFA, and linoleic acid consumptions with significant liver fibrosis risk. However, other dietary fatty acids did not show the statistically significant association with significant liver fibrosis. In conclusion, dietary linoleic acid may play a key role in the inverse association between the unsaturated to saturated fatty acid ratio and the risk of significant liver fibrosis. Further studies are needed to confirm these findings.